Plan de negocios para la fabricación de muebles personalizados y multifuncionales en la ciudad de Quito - Orna Salvador, Franz Jonnatan (2013)
The present thesis is about the development of a business of customized and multifunctional manufacture of furniture in the city of Quito. The objective is to determine the acceptance of the Ecuadorian market and the viability of this line of the business. Manufacture of Furniture in the city of Quito is quite wide. With a great amount of classic shops and some other modern ones. People nowadays look for to acquire different kind of furniture, which has an added value added and a more customized design that can fit in the style of their home. Certain furniture stores lack technology and they cannot offer products of high quality. Therefore the client is more demanding and looks for furniture that fulfills all the requirements from a good design to an excellent raw material. The market segments which will be tried are homes of any part of the city. The furniture shop will be located near Itchimbia park and the warehouse will be located near Carolina park. The employees will be constituted by ten people, between manufactures and office staff. The financial analysis of the business was realized for the first two years. The initial investment is USD 77.526,44, of which 31% will be financed with equity capital and 69% by debt. In this scenery the VAN is of USD 111.926,32 and the TIR is of 89,53%, with a rate of discount of the 15,50%. Therefore, it concludes that the business is viable.